Answer:
10x^2 - 11x - 6
Step-by-step explanation:
(5x+2)(2x-3)
= 10x^2 - 15x + 4x - 6
= 10x^2 - 11x - 6
Where yo mamas attttt , 5-(4)= 23
Answers:
A ' = (-2, -3)
B ' = (0, -3)
C ' = (-1, 1)
=======================================================
Explanation:
To apply an x axis reflection, we simply change the sign of the y coordinate from positive to negative, or vice versa. The x coordinate stays as is.
Algebraically, the reflection rule used can be written as ![(x,y) \to (x,-y)](https://tex.z-dn.net/?f=%28x%2Cy%29%20%5Cto%20%28x%2C-y%29)
Applying this rule to the three given points will mean....
- Point A = (-2, 3) becomes A ' = (-2, -3)
- Point B = (0, 3) becomes B ' = (0, -3)
- Point C = (-1, -1) becomes C ' = (-1, 1)
The diagram is provided below.
Side note: Any points on the x axis will stay where they are. That isn't the case here, but its for any future problem where it may come up. This only applies to x axis reflections.
Best Answer:<span> </span><span>So first we need both areas, then we can relate them, and then divide the circle by the square:
A(circle) = πr^2
A(square) = L*W or (2r)*(2r) which is (2r)^2
For the square, we know this is true because because the radius is half the diameter, so if we multiply the radius by 2, we get the length of one side of the square. We also know that the lengths of both sides of the square are the same by definition of a square.
Ratio: (πr^2)/(4r^2) = π/4</span>